Perceived Social Support and Life Satisfaction in Infertile Women Undergoing Treatment: A Moderated Mediation Model - Chu, Xiying; Geng, Yaoguo; Zhang, Ruiping; Guo, Wenjing (Frontiers in Psychology, 2021)
Perceived social support is positively related to life satisfaction in infertile women. Whereas, the underlying mechanism of this relationship is unclear. The present study aimed to investigate whether self-compassion mediated the relationship of perceived social support with life satisfaction and whether infertility self-efficacy moderated the relationship between perceived social support and self-compassion in infertile women. A total of 290 infertile women in mainland China undergoing treatment completed an online survey assessing perceived social support, life satisfaction, self-compassion, and infertility self-efficacy. The results supported the mediation model that perceived social support was associated with life satisfaction via self-compassion. Besides, infertility self-efficacy moderated the relationship between perceived social support and self-compassion. Specifically, perceived social support displayed a stronger predictive effect on self-compassion when infertile women had higher level of infertility self-efficacy.